Does wintering north or south of the Sahara correlate with timing and breeding performance in black‐tailed godwits?. Issue 8 (21st March 2017) - Kentie, Rosemarie; Marquez‐Ferrando, Rocío; Figuerola, Jordi; Gangoso, Laura; Hooijmeijer, Jos C.E.W.; Loonstra, A. H. Jelle; Robin, Frédéric; Sarasa, Mathieu; Senner, Nathan; Valkema, Haije; Verhoeven, Mo A.; Piersma, Theunis
Abstract: Migrating long distances requires time and energy, and may interact with an individual's performance during breeding. These seasonal interactions in migratory animals are best described in populations with disjunct nonbreeding distributions. The black‐tailed godwit ( Limosa limosa limosa ), which breeds in agricultural grasslands in Western Europe, has such a disjunct nonbreeding distribution: The majority spend the nonbreeding season in West Africa, while a growing number winters north of the Sahara on the Iberian Peninsula. To test whether crossing the Sahara has an effect on breeding season phenology and reproductive parameters, we examined differences in the timing of arrival, breeding habitat quality, lay date, egg volume, and daily nest survival among godwits (154 females and 157 males), individually marked in a breeding area in the Netherlands for which wintering destination was known on the basis of resightings. We also examined whether individual repeatability in arrival date differed between birds wintering north or south of the Sahara. Contrary to expectation, godwits wintering south of the Sahara arrived two days earlier and initiated their clutch six days earlier than godwits wintering north of the Sahara. Arrival date was equally repeatable for both groups, and egg volume larger in birds wintering north of the Sahara. Despite these differences, we found no association between wintering location and the quality of breeding habitat or nest survival. This suggests that the crossing of an important ecological barrier and doubling of the migration distance, twice a year, do not have clear negative reproductive consequences for some long‐distance migrants. Abstract : In this manuscript, we show that individuals of a long‐distance migrating shorebird (the black‐tailed godwit Limosa limosa) which spend their nonbreeding period in West Africa arrived and laid earlier than godwits migrating to wintering locations north of the Sahara, mainly in Doñana Wetlands, Spain. This contrasts with previously studied migrating bird species where migration distance tends to be positively correlated with arrival and/or laying date. In spite of their late arrival and laying, godwits which wintered closer to their Dutch breeding grounds laid larger eggs. We could, however, not find a correlation with other reproductive parameters.